Unraveling the causal link: fatty acids and inflammatory bowel disease - Zhou, Yi; Zhou, Zhenhua (Frontiers in Immunology, 2024)
Background: Previous observational studies have revealed the strong relationship between fatty acids (FA) and inflammatory bowel disease (IBD). Nonetheless, due to the inherent limitations of retrospective research, the causality between the two has not been clearly established.Methods: Genetic variants associated with the 17 FA indicators were derived from genome-wide association studies. Summary statistics for the discovery cohort and testing cohort for IBD, including ulcerative colitis (UC) and Crohn's disease (CD), were available from IIBDGC and FinnGen, respectively. Bidirectional MR analysis and sensitivity analysis with multiple measures were applied to comprehensively investigate the causal link between FA and IBD.Results: Combining the results of various MR methods, the validation of testing cohort, and the merging of meta-analysis, we demonstrated that genetically predicted Omega-3 FA levels, Ratio of Omega-3 FA to total FA, Docosahexaenoic acid (DHA) levels, and Ratio of DHA to total FA reduced the risk of IBD, UC, and CD. Meanwhile, multivariate MR suggested that the risk effects of Omega-3 FA and DHA for UC and CD were mainly affected by Saturated FA and Monounsaturated fatty acid (MUFA). Furthermore, although there was the causal association between Ratio of MUFA to total FA as well as Ratio of Polyunsaturated fatty acid (PUFA) to MUFA and CD, sensitivity analysis prompted that the findings were not robust. None of the above results had a reverse causal effect.This MR investigation provided evidence of causality between diverse FA and IBD. These findings offered new insights into the treatment and prevention of IBD.